The use mechanism of blockchain and internet of things technology in memorial architecture of smart city. (15th May 2023) - He, Chili
The purpose is to promote the development of the Internet of Things (IoT) and blockchain technology in the design of the modern memorial architecture of a smart city. First, this work perfects the system structure of the traditional intelligent building, and provides a building intelligent management framework based on IoT technology. Next, blockchain technology is used to establish an intelligent building detection system that integrates the lower-level facilities to the upper-level application information. The basic structure and software of each facility, the nodes of the IoT and the underlying intelligent components are further designed. Then, the calculation process of the system is designed, and the system model is tested. Finally, it is concluded through a calculation that MAE, MSE and MRE are 0.0203, 1.7396 and 0.5892, respectively. The model has good performance and can perform accurate tests. Moreover, the comprehensive evaluation shows that the model realises the functions of real-time data refresh, data storage, data display of each module and so on. This work is of great significance in promoting intelligent memorial architecture and smart city construction. It can further enhance the rapid development of memorial architecture in the smart city. Meanwhile, it also has important theoretical and practical significance for smart cities' comprehensive development and improvement.